Maternal knowledge on complementary feeding practices and nutritional status of children 6-23 months old, attending Kahawa west public health centre, Nairobi County - Kimwele, Angeline (My University, 2014)
Worldwide, malnutrition is responsible directly or indirectly for deaths of children under five years. Two thirds of these deaths are associated with inappropriate feeding practices. Interventions that address child malnutrition show that appropriate complementary feeding practices can save up to 6% deaths in under-fives. Attention should therefore be given to decisions taken by the mother during complementary feeding. Thus the purpose of this study was to determine mothers‟ knowledge on complementary feeding practices and relate this to the nutritional status of their children aged 6-23 months. The study adopted a cross-sectional analytical study design and was carried out at the Kahawa West Public Health Centre among the randomly sampled 286 mothers and their children. A researcher-administered questionnaire and a focus group discussion were used to collect data. Data was entered and analyzed using (SPSS version 20). Anthropometric measurements were analyzed using ENA for SMART. Chi-square test (p< 0.05) was used to show the relationships between the child‟s nutritional status and the mothers‟ knowledge on complementary feeding practices. Logistic regression was used to establish the predictors of children nutritional status in the study population. The respondents were mostly young (mean age 26.1±4.7 years), married (88.1%), housewives (66.4%) with mainly primary school level of education (47.2%). The main sources of income for most households were business (48.6%) and casual labour (31.8%). Mothers had average knowledge on complementary feeding (14.11±2.33) out of the 20 knowledge questions. All (100%) the children aged 6-8 had been introduced to solids, semi-solids and soft foods. Majority of the breast-fed children received minimum meal frequency; 6-8 months old (95.9%) and 9-23 months old (96.4%) unlike the non-breast fed children (55.0%). The percentage of children who consumed vitamin A rich foods was 60.8% and iron-rich foods were 11.5%. Over three quarters (79.0%) of the children attained the minimum dietary diversity whereas 75.9% attained the minimum acceptable diet. Overall, 13.3% of all the children were stunted, 11.9% wasted and 16.8% underweight. Maternal knowledge on complementary feeding was significantly associated with nutritional status of their children. Mothers‟ knowledge on feeding the sick and recovering children was related to underweight in children (chi-square test; p=0.026). The same was true of mothers who knew that a child‟s main meal should be diversified (chi-square test; p=0.027). There was a significant relationship between mothers‟ knowledge on duration of exclusive breastfeeding (chi-square test; p=0.022) and feeding bottles (chi-square test; p=0.005) and wasting in their children. Children who did not attain the minimum meal frequency were likely to be wasted (chi-square test; 0.001 and underweight (chi-square test; 0.013). Mothers‟ knowledge on complementary feeding practices was not significantly related to her complementary feeding practices (p>0.05). Nutrition messages on Infant and Young Child Feeding Practices should emphasis dietary diversity and frequency of feeding especially for non breastfed children and also on how to feed sick children. Nutrition programmes should pay attention to cultural beliefs on infant and young child feeding. A longitudinal study on factors that may influence complementary practices is also recommended.